Negative Emissions as the New Frontier of Photoelectrochemical CO2 Reduction. Issue 21 (16th April 2022) - May, Matthias M.; Rehfeld, Kira
Abstract: The remaining carbon budgets compatible with limiting global warming to 1.5 or 2 ° C above preindustrial levels are shrinking rapidly. An already firmly anticipated, but highly controversial measure to mitigate this challenge is the large‐scale implementation of negative emissions, removing carbon dioxide from the atmosphere. Many of the currently considered negative emission technologies (NET) are based on natural photosynthesis, associated with large land footprints. Photoelectrochemical carbon sinks, on the other hand, promise to combine high conversion efficiencies with versatile storage options. Efficient sink products differ from the products typically considered for solar fuels, which will require novel catalysts and device designs. The development of efficient devices also has to take into account climatic parameters of the local environment as especially the ambient temperature affects device operation. While still in an early stage of development, carbon drawdown by such an artificial photosynthesis approach could be a valuable extension of the portfolio of NET. Abstract : Negative CO2 emission technologies will be required to limit global warming. Photoelectrochemical approaches, converting CO2 to a sink product for safe and facile long‐term storage, are a hitherto barely explored approach to this end. In contrast to solar fuel production, energy storage is not desirable and hydrocarbons should be avoided to realize high conversion efficiencies.